2021
DOI: 10.1002/jcb.29922
|View full text |Cite
|
Sign up to set email alerts
|

Targeting sterol alpha‐14 demethylase of Leishmania donovani to fight against leishmaniasis

Abstract: Leishmaniasis is a neglected tropical disease caused by the protozoan parasite Leishmania. It is endemic in more than 89 different countries worldwide. Sterol alpha‐14 demethylase (LdSDM), a sterol biosynthetic pathway enzyme in Leishmania donovani, plays an essential role in parasite survival and proliferation. Here, we used a drug repurposing approach to virtually screen the library of the Food and Drug Administration (FDA)‐approved drugs against LdSDM to identify the potential lead‐drug against leishmaniasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 33 publications
(73 reference statements)
0
7
0
Order By: Relevance
“…For the proliferation and viability within the macrophages, Leishmania sequesters cholesterol from the cholesterol biosynthetic pathway of the host 18,20 . Ergosterol is an important sterol, a by‐product of the vital sterol biosynthetic pathway 21 . It is present in the parasite cell membrane that regulates the membrane organization and fluidity 22 .…”
Section: Introductionmentioning
confidence: 99%
“…For the proliferation and viability within the macrophages, Leishmania sequesters cholesterol from the cholesterol biosynthetic pathway of the host 18,20 . Ergosterol is an important sterol, a by‐product of the vital sterol biosynthetic pathway 21 . It is present in the parasite cell membrane that regulates the membrane organization and fluidity 22 .…”
Section: Introductionmentioning
confidence: 99%
“…Bazedoxifene is also good. Generally, lead compounds that had selectivity index values higher than 10 were regarded as promising 35 …”
Section: Resultsmentioning
confidence: 99%
“…The SI of all three compounds was found to be more compared with the SI of the Miltefosine in the case of promastigote, but in the case of intramacrophagic amastigote, only the compound Abemaciclib and Vorapaxar showed more SI value than Miltefosine. Overall, All compounds except Amyral and Imatinib demonstrated good antileishmanial activities with less cytotoxicity to mammalian cells as their selectivity index in the case of both promastigote and amastigote was found to be more than 10 35 . But among them, Abemaciclib showed the highest difference in free binding energy, 4.92 kcal/mol, with a free binding energy of human citrate synthase in molecular docking and also showed −203.47 ± 137.75 kJ/mol free binding energy in MMPBSA assay after MD simulation which indicates that this compound had a stable and strong binding affinity with the active site of citrate synthase.…”
Section: Discussionmentioning
confidence: 96%
“…These pathways and enzymes are precisely targeted via drug repurposing to treat leishmanial infection (Table 1) [18]. Studies reported that targeting enzymes involved in leishmanial sterol biosynthesis could significantly decrease parasite survival in the host [16], [22], [153]. Anti-malarial drugs like Spiro-indolone and spiro oxiindoles (JS87) target the enzyme SEs [22].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, an electronic assessment of the FDA-approved drug library against L. donovani sterol alpha-14 demethylase using a drug repurposing approach suggested that Avodart significantly reduced the number of intra-macrophagic amastigotes. Avodart-induced ROS caused apoptosislike cell death in the parasites, which was identified by annexin V/PI staining [25].…”
Section: Sterol Biosynthetic Pathwaymentioning
confidence: 99%